Compression garments and recovery from exercise-induced muscle damage: a meta-analysis. Issue 18 (11th June 2013) - Hill, Jessica; Howatson, Glyn; van Someren, Ken; Leeder, Jonathan; Pedlar, Charles
Abstract : The purpose of the study was to determine the effects of compression garments on recovery following damaging exercise. A systematic review and meta-analysis was conducted using studies that evaluated the efficacy of compression garments on measures of delayed onset muscle soreness (DOMS), muscular strength, muscular power and creatine kinase (CK). Studies were extracted from a literature search of online databases. Data were extracted from 12 studies, where variables were measured at baseline and at 24 or 48 or 72 h postexercise. Analysis of pooled data indicated that the use of compression garments had a moderate effect in reducing the severity of DOMS (Hedges' g=0.403, 95% CI 0.236 to 0.569, p<0.001), muscle strength (Hedges' g=0.462, 95% CI 0.221 to 0.703, p<0.001), muscle power (Hedges' g=0.487, 95% CI 0.267 to 0.707, p<0.001) and CK (Hedges' g=0.439, 95% CI 0.171 to 0.706, p<0.001). These results indicate that compression garments are effective in enhancing recovery from muscle damage.